2003
DOI: 10.4049/jimmunol.170.6.3386
|View full text |Cite
|
Sign up to set email alerts
|

A Broad-Spectrum Caspase Inhibitor Attenuates Allergic Airway Inflammation in Murine Asthma Model

Abstract: Asthma is characterized by acute and chronic airway inflammation, and the severity of the airway hyperreactivity correlates with the degree of inflammation. Many of the features of lung inflammation observed in human asthma are reproduced in OVA-sensitized/challenged mice. T lymphocytes, particularly Th2 cells, are critically involved in the genesis of the allergic response to inhaled Ag. In addition to antiapoptotic effects, broad-spectrum caspase inhibitors inhibit T cell activation in vitro. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…71). For example, zVAD diminished mouse T cell proliferation, but not activation (72), and a recent study in an asthma mouse model attributed the beneficial in vivo effects of zVAD to the inhibition of T cell activation (73). In our hands, the levels of LCMV-specific CD8 ϩ T cells were similar in zVAD-treated and nontreated mice at all times, and our data do not support a major role for caspases in T cell proliferation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…71). For example, zVAD diminished mouse T cell proliferation, but not activation (72), and a recent study in an asthma mouse model attributed the beneficial in vivo effects of zVAD to the inhibition of T cell activation (73). In our hands, the levels of LCMV-specific CD8 ϩ T cells were similar in zVAD-treated and nontreated mice at all times, and our data do not support a major role for caspases in T cell proliferation.…”
Section: Discussionsupporting
confidence: 55%
“…In brief, cells from blood, lymph nodes, or spleens of LCMV-infected or naive mice were isolated as described above, then were incubated in round-bottom 96-well plates at 37°C, 5% CO 2 , for 5-7 h in the presence or absence of peptide in RPMI 1640 (containing 5-10% FBS, 100 M 2-ME, L-glutamine, and antibiotics). The peptides, used at a final concentration of 1-2 g/ml, represent dominant and subdominant CD8 ϩ T cell epitopes from LCMV: NP 118 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] and NP 309 -328 (both H-2A b ). Brefeldin A (Sigma) was added to a final concentration of 5 g/ml.…”
Section: Intracellular Cytokine Staining (Iccs)mentioning
confidence: 99%
“…Finally, consistent with the observation that the activation of caspases can occur rapidly in vivo, e.g., within 2 hours in renal I/R (38), we found that caspase inhibitor Z-VAD-fmk and noncleavable PARP-1 show a protective effect in our I/R models. These findings are reminiscent of previous studies showing that caspase inhibitors attenuate the mouse response to septic shock, focal and renal I/R, and allergic airway inflammation in the asthma model (38)(39)(40)(41)(42)(43). Although each of these studies has proposed a different mechanism, all of them are linked to the prevention of cell apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…Application of caspase inhibitors has been shown to attenuate intestinal and renal tissue injuries (in our study) and other pathophysiological processes (39)(40)(41)(42)(43). The present study, using a genetically engineered mouse model, in which PARP-1 cleavage is abolished, provides novel insights into the significance of caspase cleavage of PARP-1 and highlights the importance of PARP-1 in inflammation and tissue injury.…”
Section: Discussionmentioning
confidence: 78%
“…R odent models for human allergies, including atopic dermatitis (1), asthma (2), allergic rhinitis (3), and food allergies (4,5), have allowed researchers to elucidate important fundamental principles of the cellular and molecular mechanisms of these diseases. However, it was suggested that animal models do not always reflect all aspects of human allergic diseases because of differences between species.…”
mentioning
confidence: 99%